Maternal and neonatal factors associated with mode of delivery under a universal newborn hearing screening programme in Lagos, Nigeria - Solanke Olumuyiwa A; Olusanya Bolajoko O (BMC, 2009)
Abstract Background Emerging evidence from a recent pilot universal newborn hearing screening (UNHS) programme suggests that the burden of obstetric complications associated with mode of delivery is not limited to maternal and perinatal mortality but may also include outcomes that undermine optimal early childhood development of the surviving newborns. However, the potential pathways for this association have not been reported particularly in the context of a resource-poor setting. This study therefore set out to establish the pattern of delivery and the associated neonatal outcomes under a UNHS programme. Methods A cross-sectional study in which all consenting mothers who delivered in an inner-city tertiary maternity hospital in Lagos, Nigeria from May 2005 to December 2007 were enrolled during the UNHS programme. Socio-demographic, obstetric and neonatal factors independently associated with vaginal, elective and emergency caesarean deliveries were determined using multinomial logistic regression analyses. Results Of the 4615 mothers enrolled, 2584 (56.0%) deliveries were vaginal, 1590 (34.4%) emergency caesarean and 441 (9.6%) elective caesarean section. Maternal age, parity, social class and all obstetric factors including lack of antenatal care, maternal HIV and multiple gestations were associated with increased risk of emergency caesarean delivery compared with vaginal delivery. Only parity, lack of antenatal care and prolonged/obstructed labour were associated with increased risk of emergency compared with elective caesarean delivery. Infants delivered by vaginal method or by emergency caesarean section were more likely to be associated with the risk of sensorineural hearing loss but less likely to be associated with hyperbilirubinaemia compared with infants delivered by elective caesarean section. Emergency caesarean delivery was also associated with male gender, low five-minute Apgar scores and admission into special care baby unit compared with vaginal or elective caesarean delivery. Conclusions The vast majority of caesarean delivery in this population occur as emergencies and are associated with socio-demographic factors as well as several obstetric complications. Mode of delivery is also associated with the risk of sensorineural hearing loss and other adverse birth outcomes that lie on the causal pathways for potential developmental deficits.